Clinical case of warfarin use in a patient with cardiovascular pathology - Mavluda Qadamova; Afanaseva, Inna (The Ukrainian Scientific Medical Youth Journal, 2026)
Introduction. The use of warfarin in patients with mechanical heart valve prostheses is an important component of thromboembolic prevention; however, it is associated with clinically significant drug interactions and hemorrhagic complications. Particular attention should be paid to patients with comorbid cardiovascular diseases receiving combined antithrombotic therapy. Aim. The aim of this study was to substantiate the importance of clinical and pharmaceutical support in warfarin therapy in a patient with a mechanical mitral valve prosthesis. Materials and Methods. A retrospective analysis of the medical records of a 52-year-old patient with chronic rheumatic heart disease after mitral valve replacement was performed. Clinical and pharmaceutical analysis of pharmacotherapy, assessment of international normalized ratio (INR) dynamics, and evaluation of potential interactions of warfarin with acetylsalicylic acid, omeprazole, and atorvastatin were carried out. Results. INR fluctuations within the range of 1.8–3.14 required warfarin dose adjustment. The most clinically significant interaction was identified between warfarin and acetylsalicylic acid, which increased the risk of hemorrhagic complications. Regular INR monitoring allowed stabilization of hemostatic parameters and improvement of the patient’s clinical condition. Conclusions. This clinical case illustrates the importance of individualized anticoagulant therapy and clinical and pharmaceutical monitoring to ensure treatment safety in patients receiving warfarin.